New routes in the study of Aviation and Aeronautical English - Tosqui-Lucks, Patrícia; Prado, Malila Carvalho de Almeida (The ESPecialist, 2020)
We begin this editorial inspired by the words of Santos Dumont, the Brazilian most illustrious aviator, “a flying poet, a dreaming and persevering designer, who through his creations made a difference to history, and who is therefore able to teach us lessons even today (BORGES, 2016, p. 01). Indeed, this project of an Aviation English[1] special edition began as a dream and took us a dose of perseverance to be accomplished. The idea was sparked two years ago, when we were launching the book of our research group GEIA[2], entitled Pesquisas sobre Inglês Aeronáutico no Brasil (SCARAMUCCI, TOSQUI-LUCKS, DAMIÃO, 2018), during the 5th GEIA Seminar, in Salvador, Bahia, Brazil. At that moment, we wanted to gather research results from the dissertations and theses of GEIA[3]members, most of them written in Portuguese, since it is a policy of most Brazilian Federal and State Universities, at least in the area of Linguistics and Applied Linguistics, that they are written in our national language. We felt fulfilled to share our findings with the aviation English community in Brazil, but it was about time to dream bigger and share our research results with the international community. [1] Some authors use Aviation English and Aeronautical English with capital letters, while others prefer aviation English and aeronautical English. We consider it just a stylistic choice. [2] GEIA stands for Grupo de Estudos em Inglês Aeronáutico (Aeronautical English Research Group), located at the Airspace Control Institute (ICEA), in Brazil, and validated by the National Council for Scientific and Technological Development (Conselho Nacional de Desenvolvimento Científico e Tecnológico -CNPq) since 2013. [3] The publications of group members are constantly updated on our website: https://geia.icea.gov.br/geia/papers.php